The Impact of Work Stress and Communication on Lecturer Performance: Mediating Role of Job Satisfaction - Astutik, Yuli; Kartika, Chandra; Wibowo, Nugroho Mardi (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
This study aims to examine the impact of work stress, communication, and workability on lecturer performance in Islamic higher education institutions, with job satisfaction as a mediator, and to identify the reciprocal relationship between these factors to improve lecturer performance. This study uses a quantitative design with a correlational approach. Data were collected through a survey involving 100 lecturers, who were selected using a purposive sampling technique. Data analysis was conducted using multiple regression analysis via SmartPLS software. The study’s findings indicate that work stress does not have a direct impact on job satisfaction (T-statistic = 0.518), but it does negatively affect lecturer performance (T-statistic = 4.573). Communication is proven to have a significant effect on job satisfaction (T-statistic = 3.172) and lecturer performance (T-statistic = 2.203). Workability also has a positive impact on job satisfaction (T-statistic = 2.210) and lecturer performance (T-statistic = 3.511). Job satisfaction shows a positive influence on lecturer performance (T-statistic = 3.811). This study highlights the importance of educational institutions in managing work stress, enhancing communication between lecturers, and providing training that can improve lecturers’ work ability and job satisfaction as a strategy to enhance their performance.